Household strategies for coping with the financial costs of healthcare in Edo State, Nigeria (2015)
The cross-sectional survey design was used in the 'Study to elicit "data in Edo State, Nigeria to assess the strategies employed by households to cope with the financial costs of healthcare. Questionnaire data were collected from 508 household respondents in three randomly-selected Local Government Areas of the state including Esan-west, Etsako-west and Egor. Twelve Focus Group Discussions complemented survey data. The main strategies to cope with the financial costs' of health care were mobilization of cas1i and savings (40.5%), and sale of produce and assets (16.0%). Level of income was a significant factors, affecting the ability to mobilize cash and savings to cope with the financial costs of health care (X2 = 31.787, 4df, p<0.05, critical value = 9.49). Diversion of money intended for food, education; -and clothes to cope with the financial costs of health care was common, relatively, to respondents with low income level (X2 = 13.050, 4df, p<0.05, critical value = 9.94). The findings of the study indicate that urban households have the ability to cope with the financial costs of health care, than rural households. It is therefore imperative that government should not only make healthcare facilities available but should also alleviate poverty in society to enable people defray the cost of healthcare with minimal effort.